Odours stimulate neuronal activity in the dorsolateral area of the hippocampal formation during path integration - Jorge, P E; Phillips, J B; Gonçalves, A; Marques, P A M; Nĕmec, P (Proceedings. Biological sciences, 2014)
The dorsolateral area of the hippocampal formation of birds is commonly assumed to play a central role in processing information needed for geographical positioning and homing. Previous work has interpreted odour-induced activity in this region as evidence for an 'olfactory map'. Here, we show, using c-Fos expression as a marker, that neuronal activation in the dorsolateral area of the hippocampal formation of pigeons is primarily a response to odour novelty, not to the spatial distribution of odour sources that would be necessary for an olfactory map. Pigeons exposed to odours had significantly more neurons activated in this area of the brain than pigeons exposed to filtered air with odours removed. This increased activity was observed only in response to unfamiliar odours. No change in activity was observed when pigeons were exposed to home odours. These findings are consistent with non-home odours activating non-olfactory components of the pigeon's navigation system. The pattern of neuronal activation in the triangular and dorsomedial areas of the hippocampal formation was, by contrast, consistent with the possibility that odours play a role in providing spatial information.
Keywords: čichová percepce; ptačí proteiny; protoonkogenní proteiny c-fos; Spatial Navigation; genetické markery; Odorants; pigeon; Hippocampus; Avian Proteins; zvířata; hipokampus; odoranty; olfactory activation; Columbidae; Olfactory Perception; Genetic Markers; homing; navigation; prostorová navigace; Animals; immediate early genes; Proto-Oncogene Proteins c-fos; hippocampus